Current status and needs for changes in critical care training: the voice of the young cardiologists. Issue 1 (6th January 2021) - Czerwińska-Jelonkiewicz, Katarzyna; Montero, Santiago; Bañeras, J; Wood, A; Zeid, A; De Rosa, S; Guerra, F; Tica, O; Serrano, F; Bohm, A; Ahrens, I; Gierlotka, M; et al.
Abstract: Aims: The implementation of the 2013 European Society of Cardiology (ESC) Core Curriculum guidelines for acute cardiovascular care (acc) training among European countries is unknown. We aimed to evaluate the current status of acc training among cardiology trainees and young cardiologists (<40 years) from ESC countries. Methods and results: The survey (March–July 2019) asked about details of cardiology training, self-confidence in acc technical and non-technical skills, access to training opportunities, and needs for further training in the field. Overall 614 young doctors, 31 (26–43) years old, 55% males were surveyed. Place and duration of acc training differed between countries and between centres in the same country. Although the majority of the respondents (91%) had completed their acc training, the average self-confidence to perform invasive procedures and to manage acc clinical scenarios was low—44% (27.3–70.4). The opportunities for simulation-based learning were scarce—18% (5.8–51.3), as it was previous leadership training (32%) and knowledge about key teamwork principles was poor (48%). The need for further acc training was high—81% (61.9–94.3). Male gender, higher level of training centres, professional qualifications of respondents, longer duration of acc/intensive care training, debriefings, and previous leadership training as well as knowledge about teamwork were related to higher self-confidence in all investigated aspects. Conclusions: The current cardiology training program is burdened by deficits in acc technical/non-technical skills, substantial variability in programs across ESC countries, and a clear gender-related disparity in outcomes. The forthcoming ESC Core Curriculum for General Cardiology is expected to address these deficiencies.